2016
DOI: 10.1002/anie.201604364
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Catalyzed Introduction of Azide at Tyrosine for Peptide Modification

Abstract: We show that DNA enzymes (deoxyribozymes) can introduce azide functional groups at tyrosine residues in peptide substrates. Using in vitro selection, we identified deoxyribozymes that transfer the 2′-azido-2′-deoxyadenosine 5′-monophosphoryl group (2′-Az-dAMP) from the analogous 5′-triphosphate (2′-Az-dATP) onto the tyrosine hydroxyl group of a peptide, which is either tethered to a DNA anchor or free. Some of the new deoxyribozymes are general with regard to the amino acid residues surrounding the tyrosine, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Deoxyribozymes can catalyse the nucleophilic attack of tyrosine on a triphosphate and they have been exploited to facilitate the ligation of tyrosine with a 5′-triphosphorylated RNA 57 , 58 and 2′-azido-2′-deoxyadenosine 5′-triphosphate. 59 The reaction results in an RNA–peptide conjugate or introduction of an azide group to enable further modification ( Scheme 8a ). Although high selectivity was achieved, with some deoxyribozymes being able to discriminate between two tyrosine residues on a single peptide, a lengthy selection process is needed in order to find an efficient catalyst in the first place, which makes the method inefficient in terms of time and cost.…”
Section: Chemoenzymatic Approaches For Tyrosine Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Deoxyribozymes can catalyse the nucleophilic attack of tyrosine on a triphosphate and they have been exploited to facilitate the ligation of tyrosine with a 5′-triphosphorylated RNA 57 , 58 and 2′-azido-2′-deoxyadenosine 5′-triphosphate. 59 The reaction results in an RNA–peptide conjugate or introduction of an azide group to enable further modification ( Scheme 8a ). Although high selectivity was achieved, with some deoxyribozymes being able to discriminate between two tyrosine residues on a single peptide, a lengthy selection process is needed in order to find an efficient catalyst in the first place, which makes the method inefficient in terms of time and cost.…”
Section: Chemoenzymatic Approaches For Tyrosine Modificationmentioning
confidence: 99%
“…In addition, the method works best when the substrate is tethered to the deoxyribozyme through a complementary DNA anchor. Without this tethering, which necessitates pre-modification, 14% and 59% azide-functionalization were achieved for the 32-mer salmon calcitonin (sCT) and a 28-mer fragment of atrial natriuretic peptide (atriopeptin, ANP), respectively, over 24 h. 59 Both azido-peptides were successfully modified further using CuAAC. A slightly different approach used a hexahistidine tag (His 6 ) on the untethered peptide 46 in combination with a DNA anchor complementary to part of the deoxyribozyme and linked to three nitrilotriacetic acid (NTA) units 47 .…”
Section: Chemoenzymatic Approaches For Tyrosine Modificationmentioning
confidence: 99%
“…For several other DNAzyme-catalyzed activities, we previously found that performing in vitro selection using a peptide substrate with mixed amino acid composition led to DNAzymes that require those specific peptide sequences in their substrates. 22,74,78 By analogy, we anticipate that for DNAzymecatalyzed peptide Lys acylation, future selection experiments using mixed-composition Lys-containing peptides will provide sequence-selective Lys-acylating DNAzymes, including those that function with free peptide substrates when an appropriate selection pressure is imposed. 74 Expanding the substrate tolerance of such DNAzymes from peptides to proteins is a further challenge, but worth undertaking considering the difficulty inherent to achieving nonenzymatic site-selective Lys modification of native proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The DNAzymes present in the database are classified according to the reaction that they catalyze, namely: RNA cleavage ( 1 , 7 ), DNA cleavage ( 9 , 22 ), RNA ligation ( 6 , 23–25 ), DNA ligation ( 24 , 26 ), DNA site-specific depurination ( 27 ), Porphyrin metalation ( 28 , 29 ), DNA phosphorylation ( 30 , 31 ), DNA capping ( 32 ), amino acid side-chain modification ( 9 , 33 , 34 ), thymine dimer repair ( 35 , 36 ), Copper-mediated Azide-Alkyne Cycloaddition (CuAAC) ( 37 ), Dephosphorylation ( 38 ), Diels-Alder ( 39 ), Tyrosine azido‐adenylylation ( 40 ), Modification of Phosphorylated Amino Acid Side Chains ( 41 , 42 ), Tyrosine Phosphorylation ( 43 , 44 ), Glycosylation ( 45 ), Reductive amination ( 46 ), Amide hydrolysis ( 47 , 48 ), and Ester hydrolysis ( 48 ). This classification allows users to apply filters while browsing the DNAzymes page, which can be accessed from the toolbar and from the quick links on the Home page.…”
Section: Database Contentmentioning
confidence: 99%